A Comparison of Serological and Bacteriological Methods for Detection of Mycloplasma gallisepticum in Experimentally-Infected Chickens - USAMAH AFIFF (Indonesian Society for microbiology, 2010)
An indirect enzyme-linked immunosorbent assay (ELISA) was developed to detect antibodies to Mycoplasma gallisepticum. Three antigens were used in this experiment. Antigen 1 was prepared from whole cell of M. gallisepticum, antigen 2 was a sodium dodecyl sulfate-solubilized preparation from whole cells, and antigen 3 was prepared by sonication of the whole cell antigen. The assay was then used to detect (anti)-M. gallisepticum antibodies in experimentally-infected chickens compared with serum-plate-agglutination (SPA), haemagglutination-inhibition (HI) tests, and tracheal culture. Data obtained in this experiment showed that there was a correlation between seropositivity and rate of isolation of M. gallisepticum. ELISA was found to be less sensitive, but more specific than SPA, and more sensitive than the HI test. The whole cell antigen gave the highest optical densities but was less specific than the other two antigens. The ELISA using all three antigens successfully identified the M. gallisepticum-infected chickens uniformly and positively through 14-35 days post infection, and correctly identified the control group as negative through the 35 day experimental period. The ELISA obviously has a place in the serodiagnosis of avian mycoplasma. Improved-specificity and -sensitivity of the M. gallisepticum antigen is desirable.